City develops software, available to all. - Raflo, Brook (American City & County, 2002)
The Parks Department of Springfield, Missouri, has developed an automated tracking system, the Mobile Community Tree Inventory System, to monitor tree inventories. Operating on handheld personal digital assistants, the system enables users to gather tree data quickly and download to a desktop computer with a touch of a button.